Transformasi Komunikasi Digital : Upaya Untuk Meningkatkan Kinerja Koperasi: Studi Kasus Pada Koperasi Ghani Mandiri Indonesia Cimahi Jawa Barat - Febryansyah, Yudhistira (Koaliansi : Cooperative Journal, 2021)
Koperasi Ghani Mandiri Indonesia is one of the service cooperatives based on sharia, which is engaged in aqiqah, qurban and umrah savings services. The Ghani Mandiri Indonesia Cooperative itself is a relatively new cooperative and is looking to develop, but on the other hand, this cooperative is preparing digital services in the form of applications that will be presented to Android and iOS users for service to members. The purpose of this research is to find out the transformation of digital communication that will be implemented by the cooperative, to know the digital implementation Cooperative service and to know the service model using the application that will be implemented. The method used is a case study method, with descriptive qualitative data analysis. The results of this study are a transformation of digital communication that will be applied in the form of a service using an application in an effort to improve cooperative performance, the strategy carried out is not good enough because it has several technical obstacles, then regarding the factors that can improve performance in cooperative services it can be said to get full support from members regarding the plan to implement digital services for members, namely in the form of applications that have passed the trial stage although there are still many improvements notes. From all results researched, the digital communication strategy that will be applied is not good because there are still many obstacles in its development.